Value Added Umbi Talas mejadi Keripik Talas Pada Home Industri di Kecamatan Pegantenan, Pamekasan - Mohammad Shoimus Sholeh; Endang Tri Wahyurini; Nasir Nasir (Universitas Islam Kadiri, 2022)
The root crop that is widely cultivated by farmers in Pegantenan District is the taro tuber. Some farmers carry out post-harvest processing of taro tubers to increase tuber durability. One of them is by processing it into taro chips which is expected to increase the selling value of commodities and farmers' income. The research objective is to calculate the advantages and added value of the home industry processing taro tubers into taro chips. The analytical method used is the calculation of the Value added Hayami method. From the research results, it was found that the profit received was Rp. 234,571.00 per production process in one day. The added value obtained is Rp. 9,571.00 / kilogram of the raw materials used. This added value is an advantage that is obtained by the home industry of taro root chips in 1 kilogram of the use of the raw material for taro tubers to produce taro tuber chips.